The Form of Structural Racism in the Labor Market (Global Journal of Human-Social Science, 2025)
This article seeks to present how the formation of Brazil had as a development project the reproduction of racial discrimination against the black people. Structural racism is the systematic practice of disadvantage based on race, impacting all public and private relations. How did the change in the slavery form of production to structural racism impact the Brazilian labour market? Specifically, the article presents the form of anti-black racism in the labour market, its naturalization with the debates on national identity and white superiority are organization the inferiozation of black people.
Keywords: structural racism; labour market; white superiority; inequality